2010
DOI: 10.1146/annurev.physiol.010908.163111
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death in the Pathogenesis of Heart Disease: Mechanisms and Significance

Abstract: Cell death was once viewed as unregulated. It is now clear that at least a portion of cell death is a regulated cell suicide process. This type of death can exhibit multiple morphologies. One of these, apoptosis, has long been recognized to be actively mediated, and many of its underlying mechanisms have been elucidated. Moreover, necrosis, the traditional example of unregulated cell death, is also regulated in some instances. Autophagy is usually a survival mechanism but can occur in association with cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
519
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 660 publications
(547 citation statements)
references
References 163 publications
11
519
0
17
Order By: Relevance
“…Autophagy means self-eating in Greek and can function as an intracellular recycling system by which intracellular contents and damaged organelles undergo degradation through their sequestration within autophagosomes and lysosomal degradation to supply energy substrates. [145][146][147][148][149][150][151][152][153] mTORC1 is a critical negative regulator of autophagy. 40,59,154 mTORC1 phosphorylates and inhibits the autophagy-activating kinase ULK1.…”
Section: Hk-ii-mediated Regulation Of Mtorc1 and Autophagymentioning
confidence: 99%
“…Autophagy means self-eating in Greek and can function as an intracellular recycling system by which intracellular contents and damaged organelles undergo degradation through their sequestration within autophagosomes and lysosomal degradation to supply energy substrates. [145][146][147][148][149][150][151][152][153] mTORC1 is a critical negative regulator of autophagy. 40,59,154 mTORC1 phosphorylates and inhibits the autophagy-activating kinase ULK1.…”
Section: Hk-ii-mediated Regulation Of Mtorc1 and Autophagymentioning
confidence: 99%
“…A similar difference in mir-29a(4) expression between fetal and adult skeletal muscle indicates a more ubiquitous antiproliferative role of mir-29a(4). Of note, HF is associated with loss of cardiomyocytes (43) and the mammalian heart has a very limited regenerative capacity (44). The reactivation of self-repair mechanisms by targeting miRNAs represents a possible approach to enhance regeneration (45).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a role for autophagy in programmed cell death type II (nonapoptotic death) in heart disease [15,16] and indicated that excessive autophagy could lead to cell death. Valentim et al [17] showed that inhibition of autophagy, by both genetic and pharmacological inhibition of Beclin 1, reduced cell death in cardiomyocytes subjected to simulated ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%